CCL20 mediates the anti-tumor effect of vitamin D3 in p38MAPK/NF-κB signaling in colitis-associated carcinogenesis. Issue 1 (January 2021) - Xin, Yu; Wang, Hongjuan; Wang, Yanan; Xu, Weihua; Teng, Guoxin; Han, Fuyan; Guo, Jianqiang
Abstract : Vitamin D3 is beneficial in ameliorating or preventing inflammation and carcinogenesis. CCL20 is a potential therapeutic target in carcinogenesis, which mediates the protective effect of vitamin D or vitamin D analogue in autoimmune and cancer diseases. Here we aim to evaluate whether vitamin D3 plays a protective role in colitis-associated colorectal cancer (CAC) by affecting CCL20 and the molecular mechanism. Administration of azoxymethane (AOM) followed with dextran sulfate sodium (DSS) was used to simulate CAC in mouse. After 5-day DSS treatment, vitamin D3 supplementation was for 9 weeks at 60 IU/g/w. We found that dietary vitamin D3 significantly reduced the tumor number and tumor burden in mouse. In-vivo and -vitro, vitamin D3 reduced the levels of CCL20, phospho-p38 MAPK (p-p38) and phospho-NF-κB p65 (p-p65), and the transcriptional activity of NF-κB. Further studies showed that CCL20 mediated the inhibition of vitamin D3 in p38MAPK-mediated NF-κB signaling in vitro . Taken together, vitamin D3 effectively suppressed colonic carcinogenesis in AOM-DSS mouse model. Downregulation of CCL20 may contribute to the preventive effect of vitamin D3 on NF-κB activity. It may merit further clinical investigation as a therapeutic agent against CAC in humans.